Mortality and readmission in the year following hospitalization for pneumonia among US adults. (August 2021) - Averin, Ahuva; Shaff, Melody; Weycker, Derek; Lonshteyn, Alex; Sato, Reiko; Pelton, Stephen I.
Abstract: Background: Increasing evidence suggests the impact of pneumonia persists beyond hospital discharge and the acute phase of respiratory symptoms. We characterized short-term and long-term risks of mortality and hospital readmission across the adult age span and spectrum of comorbidities. Methods: Retrospective cohort design and Optum's de-identified Integrated Claims-Clinical dataset (2012–2018) were employed. Study population comprised adults who had ≥1 pneumonia hospitalization; each hospitalization ≥365 days apart was considered. Cumulative risks of all-cause mortality (from pneumonia hospitalization through 360-day post-discharge period) and all-cause hospital readmission (during 360-day post-discharge period) were summarized on an overall basis as well as by age and comorbidity profile (i.e., healthy, at-risk, high-risk). Results: Study population totaled 37, 006 patients who contributed 38, 809 pneumonia hospitalizations; mean age was 71 years, 51% were female, and 88% had at-risk (33%) or high-risk (55%) conditions. Mortality was 3.5% in hospital, 8.2% from admission to 30 days post-discharge, and 17.7% from admission to 360 days post-discharge. Hospital readmission was 12.5% during the 30-day post-discharge period, and 42.3% during the 360-day post-discharge period. Mortality risk increased with age and severity of comorbidity profile; readmission risk was highest for persons aged 65–74 years and persons with high-risk conditions. Conclusions: All-cause mortality up to 1 year following pneumonia hospitalization was substantial, and was associated with increasing age and worsening comorbidity profile. Both readmission and mortality were greater at all ages in at-risk and high-risk subgroups (vs. healthy counterparts). Strategies that prevent pneumonia and/or associated pathophysiologic changes, especially among individuals with comorbidities, have the potential to reduce morbidity and mortality. Highlights: All-cause mortality up to 1 year following pneumonia hospitalization was substantial. Readmission following pneumonia hospitalization is high up to one year after discharge. Mortality and readmission risk increased with age and severity of comorbidity profile.